Boustrophedonic Frames: Quasi-Optimal L2 Caching for Textures in GPUs - Joseph, Diya; Aragon, Juan L.; Parcerisa, Joan-Manuel; Gonzalez, Antonio (2023 32nd International Conference on Parallel Architectures and Compilation Techniques (PACT), 2023)
Literature is plentiful in works exploiting cache locality for GPUs. A majority of them explore replacement or bypassing policies. In this paper, however, we surpass this exploration by fabricating a formal proof for a no-overhead quasi-optimal caching technique for caching textures in graphics workloads. Textures make up a significant part of main memory traffic in mobile GPUs, which contributes to the total GPU energy consumption. Since texture accesses use a shared L2 cache, improving the L2 texture caching efficiency would decrease main memory traffic, thus improving energy efficiency, which is crucial for mobile GPUs. Our proposal reaches quasi-optimality by exploiting the frame-to-frame reuse of textures in graphics. We do this by traversing frames in a boustrophedonic 1 1 Boustrophedon is a style of writing in which alternate lines of writing are reversed in order. This is in contrast to most modern languages, where the order of lines is the same, usually left-to-right. manner w.r.t. the frame-to-frame tile order. We first approximate the texture access trace to a circular trace and then forge a formal proof for our proposal being optimal for such traces. We also complement the proof with empirical data that demonstrates the quasi-optimality of our no-cost proposal.